1994
DOI: 10.1007/bf02444333
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sensory input on the levels of enzymes involved in energy metabolism

Abstract: Presentation of sensory stimuli of various modalities to rats immediately before their decapitation led to a significant increase in the level of succmate dehydrogenase in the hippocampus, the magnitude of the increase being dependent on the number of stimuli presented. In each individual case, this enzyme's activity was proportional to the amplitude of the population spike recorded in the hippocampus of the same rat. An inverse relationship was noted between the rate of plastic processes in the hippocampus up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

1997
1997
1999
1999

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…Our previous studies showed that with increasing brain excitability the level of SDH activity increased by on average 20% compared with the norm [4,6]. In the present study, the increase in SDH activity was observed in ICS after 21 days and later.…”
Section: "supporting
confidence: 66%
See 3 more Smart Citations
“…Our previous studies showed that with increasing brain excitability the level of SDH activity increased by on average 20% compared with the norm [4,6]. In the present study, the increase in SDH activity was observed in ICS after 21 days and later.…”
Section: "supporting
confidence: 66%
“…2). The data obtained in other experimental models indicate that the increase in SDH activity is primarily due to its activation in astroglial cells [4]. Therefore, decreased SDH activity in this period can be explained by redistribution of glial cells.…”
Section: "mentioning
confidence: 76%
See 2 more Smart Citations